Plasma Natriuretic Peptides in Children and Adolescents with Obstructive Sleep Apnea and Their Changes Following Intervention - Li, Albert M.; Au, Chun T; Zhu, Jodie; Chan, Kate; Chan, Michael; Lee, Dennis; Wing, Yun K (Frontiers in Pediatrics, 2014)
Objective: This study aimed to evaluate circulating natriuretic peptides (NP) concentration in obese and non-obese children and adolescents with and without OSA, and their levels following OSA treatment. Methods: Subjects with habitual snoring and symptoms suggestive of OSA were recruited. They underwent physical examination and overnight polysomnography (PSG). OSA was diagnosed if obstructive apnea hypopnea index (OAHI) ≥1/h. Fasting serum atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) were taken after overnight PSG. The subjects were divided into obese, non-obese, with and without OSA groups for comparisons. Results: 114 children (77 were boys) with a median (IQR) age of 10.8 (8.3-12.7) years (range: 2.4-11.8 years) were recruited. Sixty-eight subjects were found to have OSA. Natriuretic peptide levels did not differ between subjects with and without OSA in both obese and non-obese groups. . Stepwise multiple linear regressions revealed that body mass index (BMI) z-score was the only independent factor associated with NP concentrations. Fifteen children with moderate-to-severe OSA (OAHI >5/h) underwent treatment and there were no significant changes in both ANP and BNP levels after intervention. Conclusion: BMI rather than OSA was the main determinant of natriuretic peptide levels in school-aged children and adolescents.